Model Kesetimbangan Adsorpsi Zat Warna Direct Brown menggunakan Limbah Padat Pulp Dan Kertas (Dregs) Dengan Proses Batch - Chandra Marzuki Nababan; Rozanna Sri Irianty; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Particularly, industrial waste color paper mill is one of the causes of environmental problems that require the removal of an effective and efficient. Adsorption is a separation method that is simple and easy to operation. The purpose of this research study the ability of solid waste and paper pulp (dregs) adsorb dye brown and learn direct equilibrium models adsorption against adsorbent mass variations and temperature adsorption operation. The maximum wavelength of the dye Direct Brown 417 nm. The highest removal efficiency of concentration was 93.57%. Equilibrium models corresponding to the direct-brown dye adsorption use solid waste pulp and paper (dregs) was the Langmuir isotherm. The result of correlation factor (R2) was 0.9488.Keywords : Direct dyes, dregs, adsorption, isotherms Lagmuir, correlation factor